A study on the use of modified extremity dosemeters for the measurement of Hp(3, α). (January 2021) - Dubeau, J.; Sun, J.; Leroux, N.; Atanackovic, J.; Dauer, L.T.; Witharana, S.S. Hakmana; Hanu, A.
Abstract: In most jurisdictions, the presently imposed annual eye-lens dose limits are 150 mSv for occupational and 15 mSv for the general public. These limits were based on a 1991 recommendations of the International Commission on Radiological Protection (ICRP), in its publication 60, and they were reiterated in 2007 in the ICRP publication 103. However, recent re-analyses of available epidemiological data appear to indicate that the onset of cataracts may occur at doses as low as 0.5 Gy. This led the ICRP to recommend, in the 2012 publication 118, the lowering of the annual dose limits to the lens of the eye of 20 mSv, averaged over 5 years, with no dose exceeding 50 mSv for any one year. The annual eye-lens dose limit for the general public remained at 15 mSv. The reduction of the eye-lens annual dose limit by nearly one order of magnitude led to large research efforts, including in the area of personal dose monitoring. This paper presents the results of a performance study of H p (0.07) dosemeters which were modified to allow the measurement of H p (3, α). The dosemeters were provided by four Canadian nuclear facilities, and one United States medical institution. Hence, five different technologies were tested for a variety of photon qualities and one standard beta field. The motivation to use H p (0.07) dosemeters was to show that it is possible to leverage dosimetry technologies already in place at various institutions. It was found that, using a low atomic number filter of nominally 300 mg cm −2 in mass thickness, most of the dosemeters considered would provide acceptable performances for the measurement of H p (3, α).